2011
DOI: 10.1055/s-0030-1270415
|View full text |Cite
|
Sign up to set email alerts
|

Soft Tissue Fillers and Biofilms

Abstract: The purpose of this study was to review the clinical course of reported hypersensitivity reactions associated with use of soft tissue fillers and the response of these reactions to treatment. In this comprehensive literature review, we identified ~40 published reports that together reported numerous adverse reactions associated with use of nonpermanent soft tissue fillers; however, very few of these reactions were consistent with type I immediate or type IV delayed hypersensitivity reactions. Based on their cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 42 publications
0
33
0
Order By: Relevance
“…[23][24][25] Biofilms are usually not identifiable by culture and may appear as sterile abscesses or cause a chronic inflammatory response. 26,27 Histologically, inflammatory reactions to HA injection have shown both lymphoplasmacytic and lymphocytic-macrophage infiltrates with foreignbody granulomas. 6 The appearance of inflammatory nodules in areas located at some distance from the injection site, the course of the reaction (waxing and waning), the resistance of lesions to long-term antibiotic treatment, and the negative bacterial culture and PCR assay (in 1 patient, before antibiotic treatment) are less compatible with biofilm formation and favor an immunogenic reaction as the mechanism underlying reaction to HAVb.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] Biofilms are usually not identifiable by culture and may appear as sterile abscesses or cause a chronic inflammatory response. 26,27 Histologically, inflammatory reactions to HA injection have shown both lymphoplasmacytic and lymphocytic-macrophage infiltrates with foreignbody granulomas. 6 The appearance of inflammatory nodules in areas located at some distance from the injection site, the course of the reaction (waxing and waning), the resistance of lesions to long-term antibiotic treatment, and the negative bacterial culture and PCR assay (in 1 patient, before antibiotic treatment) are less compatible with biofilm formation and favor an immunogenic reaction as the mechanism underlying reaction to HAVb.…”
Section: Discussionmentioning
confidence: 99%
“…A biofilm is a dormant bacterial infection, probably introduced during injection or related to a regional or systemic infection (e.g. dental infections), that forms a structured community of micro‐organisms surrounded by a protective barrier comprising a self‐developed polymeric matrix . These colonies adapt and maintain their integrity by evading the host's immune system through reduced metabolism and growth rates, as well as being antibiotic resistant and protected from phagocytosis by the extra‐polymeric barrier.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…Once established, biofilms are extremely difficult to completely eradicate . Although biofilms have rarely been reported with non‐permanent fillers, the prolonged longevity of HA fillers of up to 36 months suggests they may also pose a risk for biofilm complications similar to permanent fillers . Bjarnsolt and Christensen both showed that bacteria could be detected in almost any late‐onset tissue filler lesions by means of fluorescence in situ hybridization, even though standard cultures where negative.…”
Section: Adverse Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, these infections are difficult to treat, and so the focus should be on prevention. If a red, indurated area appears at any time after treatment, regardless of duration, a biofilm should be suspected 36,37. Persistent inflammatory conditions not showing improvement with other therapy and inflammatory nodules that recur after resolution may also indicate a biofilm.…”
Section: Dermal Filler Complications: Avoidance and Treatmentmentioning
confidence: 99%